Constructions of motherhood and fatherhood in newspaper articles on maternal and paternal postpartum depression. (11th April 2014) - Alexander, Elizabeth; McMullen, Linda
Abstract : Postpartum depression (PPD) is typically constructed as a medical condition that is defined by prevalence rates, time of onset, duration, symptoms, causes and treatments. Presentations of PPD in popular texts have also revealed that it is a site for constructions of mothering/motherhood. While PPD has traditionally been assumed to be the domain of women, researchers have recently focused attention on PPD and men. Using articles on maternal and paternal PPD published in Canadian and American newspapers between 2008 and 2012, we analysed how constructions of mothering/motherhood and fathering/fatherhood were inscribed in this public forum. We show how mothering/motherhood was foregrounded via dominant evaluative discourses and highly imbued with expectations while fathering/fatherhood was kept in the background and characterised by the unavailability of clear expectations. We conclude that maternal PPD remains primary and normative while paternal PPD remains 'othered' despite the supposed attention to it in these public texts.